2022
DOI: 10.3390/ijms23116229
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Mitochondrial Human Carbonic Anhydrases VA and VB as a Therapeutic Strategy against Paclitaxel-Induced Neuropathic Pain in Mice

Abstract: Neuropathy development is a major dose-limiting side effect of anticancer treatments that significantly reduces patient’s quality of life. The inadequate pharmacological approaches for neuropathic pain management warrant the identification of novel therapeutic targets. Mitochondrial dysfunctions that lead to reactive oxygen species (ROS) increase, cytosolic Ca2+ imbalance, and lactate acidosis are implicated in neuropathic pain pathogenesis. It has been observed that in these deregulations, a pivotal role is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…However, most of these therapies exhibited moderate efficacy and significant side effects such as somnolence, constipation, tolerance, and dizziness [ 60 ]. In addition, some treatments only improved neuropathy or one of the emotional disorders associated with chemotherapy-induced neuropathic pain [ 61 , 62 , 63 ], but only a few studies evaluated the possible effects of different treatments in the management of PIPN-associated mood disorders [ 13 , 64 , 65 ]. In this line, this study demonstrated that treatment with HRW inhibited neuropathy and avoided the cognitive and emotional deficits associated.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these therapies exhibited moderate efficacy and significant side effects such as somnolence, constipation, tolerance, and dizziness [ 60 ]. In addition, some treatments only improved neuropathy or one of the emotional disorders associated with chemotherapy-induced neuropathic pain [ 61 , 62 , 63 ], but only a few studies evaluated the possible effects of different treatments in the management of PIPN-associated mood disorders [ 13 , 64 , 65 ]. In this line, this study demonstrated that treatment with HRW inhibited neuropathy and avoided the cognitive and emotional deficits associated.…”
Section: Discussionmentioning
confidence: 99%
“…This is a result of increased production of free oxygen radicals aftertreatment and the release of damaged mitochondrial debris [45]. Resveratrol prevents cell survival, promotes programmed cell death in MCF-7 cells [46], and enhances the anti-cancer effects of paclitaxel in human liver cancer cells HepG22. Resveratrol induces intrinsic cell death dependent on caspases associated with increased oxidative stress mediated by oxygen and nitrogen in its cells [47].…”
Section: Resveratrol's Impact On Cellular Indicatorsmentioning
confidence: 99%
“…Indeed, connections have been observed between the activity of CAs and pain reducing HCO 3 - -dependent depolarization via GABA A receptors when the function of the neuron-specific potassium-chloride (KCl) cotransporter KCC2 is compromised [ 54 , 55 ]. The type of moiety bearing the phenol portion of the tail seems to be a crucial factor that impacts activity against different isoforms, as demonstrated in the case of hCA IX, where a phenyl moiety showed a 10-fold increase in potency compared to other reported derivatives [ 53 ].…”
Section: Five-membered Heterocyclic Sulfonamidesmentioning
confidence: 99%